2021
DOI: 10.1002/aqc.3584
|View full text |Cite
|
Sign up to set email alerts
|

El Niño–Southern Oscillation impacts on jumbo squid habitat: Implication for fisheries management

Abstract: 1. Dosidicus gigas is an ecologically and economically important squid species extensively distributed in the eastern Pacific Ocean. Its habitat is extremely sensitive to climatic and environmental variability.2. The relationship between habitat pattern of D. gigas and El Niño-Southern Oscillation (ENSO, divided into the El Niño, ENSO-neutral, and La Niña events) was assessed from 1950 to 2015, using a habitat suitability index (HSI) modelling approach including two crucial environmental variables: sea surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 67 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…Thus, it may be possible to enable long‐term forecasting of rodent outbreaks, production of animals for human use, or climatic threats to endangered species. The use of ENSO signals has been suggested for early pest management in China (Zhang & Wang, 1998; Jiang et al ., 2011) and Australia (Letnic & Dickman, 2006), for fisheries and aquaculture management in the Pacific (Bertrand et al ., 2020; Yu et al ., 2021), and for early warnings for conservation of primates in Brazil (Wiederholt & Post, 2010). Our ability to use ENSO or NAO cycles to predict animal population trajectories strongly depends on understanding the relationship of these broad‐scale climate factors to animal populations via their effects on local‐scale climate factors, and the links between these remain worthy of further investigation.…”
Section: Perspectivesmentioning
confidence: 99%
“…Thus, it may be possible to enable long‐term forecasting of rodent outbreaks, production of animals for human use, or climatic threats to endangered species. The use of ENSO signals has been suggested for early pest management in China (Zhang & Wang, 1998; Jiang et al ., 2011) and Australia (Letnic & Dickman, 2006), for fisheries and aquaculture management in the Pacific (Bertrand et al ., 2020; Yu et al ., 2021), and for early warnings for conservation of primates in Brazil (Wiederholt & Post, 2010). Our ability to use ENSO or NAO cycles to predict animal population trajectories strongly depends on understanding the relationship of these broad‐scale climate factors to animal populations via their effects on local‐scale climate factors, and the links between these remain worthy of further investigation.…”
Section: Perspectivesmentioning
confidence: 99%
“…The vulnerability across the Pacific coast is primarily affected by ENSO [19]. Overall, climate forcing of ENSO will affect physical processes [20,21], primary production [22,23], and prey-predator relations [24] in local marine ecosystems, and thereby ultimately impact habitats [25], migration patterns [26], population recruitments [27], and food webs [28], thus their effects may experience time lags before being felt via, for instance, changes in fishing efforts. Past investigations have shown that fisheries in the Pacific Ocean were strongly influenced by ENSO events, with average landings decreasing ~0.8 million tons in El Niño and increasing ~1.1 million tons in La Niña years since 1950 [29].…”
Section: Introductionmentioning
confidence: 99%